The Desmosome-Keratin Scaffold Integrates ErbB Family and Mechanical Signaling to Polarize Epidermal Structure and Function - Green, Kathleen J.; Niessen, Carien M.; Rübsam, Matthias; Perez White, Bethany E.; Broussard, Joshua A. (Frontiers in Cell and Developmental Biology, 2022)
While classic cadherin-actin connections in adherens junctions (AJs) have ancient origins, intermediate filament (IF) linkages with desmosomal cadherins arose relatively late during evolution in vertebrate organisms. In this mini-review, we discuss how overlaying the IF-desmosome network onto the existing cadherin-actin network provided new opportunities to coordinate tissue mechanics with the positioning and function of chemical signaling mediators in the ErbB family of receptor tyrosine kinases. We focus in particular on the complex multi-layered outer covering of the skin, the epidermis, which serves essential barrier and stress sensing/responding functions in terrestrial vertebrates. We will review emerging data showing that desmosome-IF connections, AJ-actin interactions, ErbB family members, and membrane tension are all polarized across the multiple layers of the regenerating epidermis. Importantly, their integration generates differentiation-specific roles in each layer of the epidermis that dictate the form and function of the tissue. In the basal layer, the onset of the differentiation-specific desmosomal cadherin desmoglein 1 (Dsg1) dials down EGFR signaling while working with classic cadherins to remodel cortical actin cytoskeleton and decrease membrane tension to promote cell delamination. In the upper layers, Dsg1 and E-cadherin cooperate to maintain high tension and tune EGFR and ErbB2 activity to create the essential tight junction barrier. Our final outlook discusses the emerging appreciation that the desmosome-IF scaffold not only creates the architecture required for skin’s physical barrier but also creates an immune barrier that keeps inflammation in check.